2015
DOI: 10.1371/journal.pone.0137593
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Epidemiology of Staphylococcus aureus among Residents of Seven Nursing Homes in Shanghai

Abstract: BackgroundResidents in nursing homes (NHs) always represent potential reservoirs for Staphylococcus aureus and methicillin-resistant S. aureus (MRSA). To our knowledge, there is no epidemiological information up till now that describes the prevalence and molecular characteristics of S. aureus in nursing home residents in Shanghai, China.MethodsFour hundred and ninety-one unique residents from 7 NHs were enrolled in this study. Specimens were collected among these residents including 491 nasal swabs, 487 axilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 37 publications
3
25
1
Order By: Relevance
“…S. aureus colonizes multiple anatomical locations and the frequency of colonization in various niches might vary depending on the methodology and the context of the study. Our study demonstrated that the anterior nares are colonized more frequently than the throat, which is consistent with the findings of previous studies on the prevalence of both MSSA and MRSA occurring together (Roghmann et al 2015;Zhang et al 2015;Peters et al 2017). Alternatively, some researchers have reported that colonization only in the throat is the most prevalent pattern (Nilsson and Ripa 2006;Hamdan-Partida et al 2010) or have observed the high prevalence of extra-nasal colonization as well, i.e., in the groin and the perianal regions (Mody et al 2008).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S. aureus colonizes multiple anatomical locations and the frequency of colonization in various niches might vary depending on the methodology and the context of the study. Our study demonstrated that the anterior nares are colonized more frequently than the throat, which is consistent with the findings of previous studies on the prevalence of both MSSA and MRSA occurring together (Roghmann et al 2015;Zhang et al 2015;Peters et al 2017). Alternatively, some researchers have reported that colonization only in the throat is the most prevalent pattern (Nilsson and Ripa 2006;Hamdan-Partida et al 2010) or have observed the high prevalence of extra-nasal colonization as well, i.e., in the groin and the perianal regions (Mody et al 2008).…”
Section: Resultssupporting
confidence: 92%
“…Staphylococcus aureus is an opportunistic human pathogen known for its increasing prevalence in both hospitals and the general community. An incremental rise in drug-resistance and high disease-causing capabilities has also been observed (Zhang et al 2015;Zurita et al 2016). The most common anatomical location for the commensal carriage of S. aureus is the anterior nares (Kluytmans et al 1997;Pollitt et al 2018), although recent epidemiological studies highlight the role of pharyngeal carriage in S. aureus transmission (Nilsson and Ripa 2006;Hamdan-Partida et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the prevalence of MRSA colonization was 1.28%, and the overall rate of S. aureus in the nasal region was 13.2%. Both of these rates were lower than the nasal carriage rates reported in other studies from China or abroad ( 1 , 9 , 18 – 22 ). MRSA incidence in elective orthopedic surgery was also lower than reported incidence in other surgeries ( 23 , 24 ).…”
Section: Discussioncontrasting
confidence: 70%
“…Two methods commonly used for the identification of S. aureus include culturing and polymerase chain reaction (PCR). Culturing the bacteria on chromogenic agar is a less expensive test, while PCR is considered the ‘gold standard' for MRSA detection ( 15 – 17 ). Our decision to use the culture method was based on the economic standpoint (less expensive for the cost of material and labor) and the desired speed to provide the test result (1–2 days).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the TSST-1 ST5 has been described in China and France before. [ 22 23 ] Besides frequently discovered among SSTIs patients in China currently, ST7 was also found to be the most common genotype of MSSA in invasive community-acquired S. aureus infection in Chinese children. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%